Optimization of the grounding system at the conocoto treatment plant, Quito - Ecuador (Agroindustria, Sociedad y Ambiente, 2020)
In any work environment, workers are exposed to physical risks, which can affect their performance, cause damage to their health, temporary disability, and even death. Among the most common accidents and risks are atmospheric electrical discharges, which are responsible for many of the deaths from work accidents due to the remaining energy that can be transmitted to equipment and buildings, so it was essential to optimize the Grounding System (SPAT) to minimize this type of work accident. In this regard, a diagnosis was made of the soil resistivity, grounding system, and lightning rod system at the Conocoto treatment plant in the canton of Quito, province of Pichincha, in order to comply with Ecuadorian biosafety regulations (IEEE 80 Std. 2000 and CTE DB-SUA 8.), which guarantee the correct sizing of the grounding meshes implemented to protect personnel from dangerous voltages and optimize the resistance value of the grounding meshes. The results found show that the use of the ground intensifier (GEMe) improved the resistivity of the soil surrounding the rods and the electrical conductor, helping to maintain its humidity regardless of the climatic seasons and reducing the risks of physical damage due to the transmission of voltages above the maximum values allowed for buildings and infrastructure resulting from electrical and atmospheric discharges. The optimization of the system implemented will reduce occupational accidents and improve the safety of workers in the water treatment system.
Keywords: accidents; biosecurity; labor regulations; occupational risks